2015
DOI: 10.1111/bju.12927
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopy for stone disease in the paediatric population: a systematic review

Abstract: The aim of the present review was to look at the role of ureteroscopy (URS) for treatment of paediatric stone disease. We conducted a systematic review using studies identified by a literature search between January 1990 and May 2013. All English-language articles reporting on a minimum of 50 patients aged ≤18 years treated with URS for stone disease were included. Two reviewers independently extracted the data from each study. A total of 14 studies (1718 procedures) were reported in patients with a mean (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…45 A higher failure rate and higher complication rate (24.0 vs. 7.1%) were noted in children <6 years old compared to those older than 6 years. 45 Given the smaller caliber ureter in children, especially in infants and toddlers, some authors have recommended pre-stenting 2–8 weeks prior to URS to passively dilate the ureter and ureterovesical junction. 46 Others, however, have shown that primary ureteroscopic access can be achieved in 50–60% of children, including those that are prepubertal, with low complication rates.…”
Section: Acute Managementmentioning
confidence: 88%
See 2 more Smart Citations
“…45 A higher failure rate and higher complication rate (24.0 vs. 7.1%) were noted in children <6 years old compared to those older than 6 years. 45 Given the smaller caliber ureter in children, especially in infants and toddlers, some authors have recommended pre-stenting 2–8 weeks prior to URS to passively dilate the ureter and ureterovesical junction. 46 Others, however, have shown that primary ureteroscopic access can be achieved in 50–60% of children, including those that are prepubertal, with low complication rates.…”
Section: Acute Managementmentioning
confidence: 88%
“…4244 One recent systemic review of URS identified 14 studies with over 1700 procedures in children aged 0.25 to 18 years old. 45 Mean stone-free rate was 87.5% and complications (Clavien I–III) were noted in 10.5% of patients including 3 patients with ureteral strictures and 18 patients with ureteral perforation (1.0%). 45 A higher failure rate and higher complication rate (24.0 vs. 7.1%) were noted in children <6 years old compared to those older than 6 years.…”
Section: Acute Managementmentioning
confidence: 91%
See 1 more Smart Citation
“…Evidence suggests that paediatric patients who undergo URS for urolithiasis have an overall SFR of 85.5–87.5% and an overall complication rate of 10.5–12.4% [18, 19]. It is worth noting that in subgroup analysis, patients below the age of 6 had a higher complication rate (24% vs. 7.1%) and failure rate (4.4% vs. 1.7%) than children over the age of 6 [18]. To achieve best outcomes, the management should be a combined multidisciplinary approach between paediatric, renal and urology teams.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review by Ishii et al found an initial URS procedure failed to reach completion in only 2.2% of children. 8 Meanwhile medical expulsive therapy has gained traction as well. 9 …”
Section: Introductionmentioning
confidence: 99%